(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
This thesis explores the impact of extensive listening on the listening comprehension skills of English as a Foreign Language (EFL) university students. Extensive listening involves consistent exposure to authentic spoken language through resources such as podcasts, audiobooks, and videos. The study examines whether this method improves students’ ability to understand spoken English, focusing on fluency, the ability to comprehend different accents, and informal language structures. The thesis concludes that extensive listening is a valuable method for enhancing listening comprehension and suggests that incorporating it into language curricula can accelerate the development of students’ listening abilities, preparing them for real-life communication in English.